Sudan. Issue 5 (1st October 2005) - Seidi, Osheik; Hussein, Abbashar
Abstract : Sudan is the largest country in Africa, occupying about one million square miles in the north east of the continent (Fig. 1). The country has a long coastline along the Red Sea, and shares boundaries with nine other countries: Egypt in the north and then clockwise with Eritrea, Ethiopia, Kenya, Uganda, Congo, Central African Republic, Chad and Libya. It is so vast in area that there are various climates and numerous rivers, the most famous of which is the Nile which has more than half its length in Sudan with its main tributaries, the Blue and White Niles meeting in Khartoum, the capital city. Sudan is a multiracial, multicultural country with a unique mixture of African and Arab tribes who have lived in harmony over the centuries, though in recent years there have been several civil wars which are principally fuelled by a struggle for power and wealth rather than